Controversies Incorporated: Bridging That Gap; The Mystic’s Point of View; The Notation of Time: A Reaction to Richard Barrett’s Reply - Ball, Andrew; Moody, Ivan; Ingram, James (Contact: A Journal for Contemporary Music (1971-1990), 1987)